2020
DOI: 10.1177/1591019920961199
|View full text |Cite
|
Sign up to set email alerts
|

Alternative route to a hypoglossal canal dural arteriovenous fistula in case of failed jugular vein approach

Abstract: Hypoglossal canal dural arteriovenous fistulas (HC-DAVF) involve the anterior condylar vein (ACV) and anterior condylar confluence (ACC). They often present with tinnitus, bruit, and hypoglossal nerve palsy. The most common treatment in HC-DAVFs is transvenous embolization using coils and the most direct transvenous route is the trans-internal jugular vein access. When this approach is not feasible, a treatment attempt is possible through alternative routes. We report 2 patients with DAVFs involving the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…And then other alternative approaches are applied. Dahl et al reported a case of successful treatment of HCDAVF by intravenous coil embolization through the deep cervical vein as an alternative access to the ACC after the failure of the trans-IJV approach ( 11 ). Diaz et al reported a case of HCDAVF in which, after embolization and surgical failure, the anterior condylar vein was punctured percutaneously at the hypoglossal foramina and occluded with onyx after placing two anchor coils ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…And then other alternative approaches are applied. Dahl et al reported a case of successful treatment of HCDAVF by intravenous coil embolization through the deep cervical vein as an alternative access to the ACC after the failure of the trans-IJV approach ( 11 ). Diaz et al reported a case of HCDAVF in which, after embolization and surgical failure, the anterior condylar vein was punctured percutaneously at the hypoglossal foramina and occluded with onyx after placing two anchor coils ( 6 ).…”
Section: Discussionmentioning
confidence: 99%